Outpatient Practice of Lipid-Lowering Therapy Prescription (According to the ARGO-3 Study) - M. V. Ezhov; N. M. Akhmedzhanov; T. E. Kolmakova; A. V. Tyurina; A. I. Martynov (Столичная издательская компания, 2023)
Aim. To study the frequency of prescriptions of various types of lipid-lowering therapy and their effectiveness in outpatient clinical practice based on the results of a questionnaire of primary care physicians.Material and methods. The study was performed in 2022 in 75 constituent entities of the Russian Federation with the participation of 1117 doctors working in outpatient clinics. Most of the doctors had work experience of 10-20 years or more. Doctors of polyclinics (therapists and cardiologists, etc.) before the start of the study received instructions, questionnaires for filling out, developed by the National Atherosclerosis Society. The frequency of prescriptions by primary care physicians of various types of lipid-lowering therapy and their effectiveness in terms of the frequency of achieving target levels of low-density lipoprotein cholesterol (LDL-C) was studied based on the results of a questionnaire.Results. Monotherapy with statins was prescribed in 55.2% of cases, free combination of rosuvastatin with ezetimibe - in 17.2%, single pill combination of rosuvastatin with ezetimibe - in 23.2%, combination therapy with PCSK9 inhibitors - in 4.1% of cases. Target levels of LDL-C ˂ 1.8 mmol/l and ˂ 1.4 mmol/l were achieved with statin monotherapy in 42.6% and 28.2% of cases, respectively, free combination of rosuvastatin with ezetimibe - in 61.7% and 39 .5%, a fixed combination of rosuvastatin with ezetimibe - in 67.8% and 48.5%, combination therapy with PCSK9 inhibitors - in 96.8% and 92.8% of cases.Conclusion. The single pill combination of rosuvastatin with ezetimibe is more effective in achieving target levels of LDL-C compared with statin monotherapy and therapy with free combination of statin with ezetimibe. Despite the fact that the target values of LDL-C when prescribing a combination with PCSK9 inhibitors were achieved in 96.8% and 92.8% of cases, they were used quite rarely at the outpatient stage of treatment in the Russian Federation.